GEICO1601-ROLANDO: a multicentric single arm Phase II clinical trial to evaluate the combination of olaparib and pegylated liposomal doxorubicin for platinum-resistant ovarian cancer. (10th January 2019) - Perez-Fidalgo, J Alejandro; Iglesias, Maria; Bohn, Uriel; Calvo, Elisa; Garcia, Yolanda; Guerra, Eva; Manso, Luis; Santaballa, Ana; Gonzalez-Martin, Antonio
Response to polyadenosine diphosphate ribose polymerase ( PARP ) inhibitors in platinum-resistant ovarian cancer and in the absence of BRCA mutations is very low. Combining PARP inhibitors with other agents might overcome this lack of activity. Here we describe the rationale and design of GEICO1601-ROLANDO (resistant ovarian cancer treated with olaparib and pegylated liposomal doxorubin; NCT03161132). ROLANDO is a Phase II single-arm multicenter trial in which patients are treated with a combination of olaparib and pegylated liposomal doxorubicin (PLD) in platinum-resistant epithelial ovarian, primary peritoneal, or Fallopian tube cancer regardless of the BRCA mutation status. The primary end point is progression-free survival at 6 months. Other secondary end points are response rate, disease control rate, quality of life and overall survival. Lay abstract: PARP inhibitors as a single agent have shown very modest activity in platinum-resistant ovarian cancer in a BRCA nonselected population. The GEICO1601-ROLANDO trial is a protocol designed with the aim of assessing efficacy and safety of the combination of olaparib and pegylated liposomal doxorubin followed by olaparib maintenance in this setting.